Bipolar Dislocation of the Clavicle: A Report of Two Cases with Different Injury Patterns and a Literature Review - Ichiro Okano; Takatoshi Sawada; Katsunori Inagaki (Case Reports in Orthopedics)
Bipolar dislocation of the clavicle is a rare injury that is defined as a concomitant dislocation of the ipsilateral acromioclavicular joint and sternoclavicular joint. This injury is also described as a floating clavicle. Although this injury has been known for nearly two centuries, knowledge about it is limited and the treatment strategy remains controversial. Bipolar dislocation includes several combinations of both joints’ injury types. We reported two patients with bipolar dislocation of the clavicle: one with an anterior dislocation and the other with a posterior dislocation of the sternoclavicular joint. After reviewing the currently available literature, we discussed these cases to highlight the necessity of a specific treatment approach that is modified based on the pattern of each joint’s lesion.